2015
DOI: 10.1620/tjem.235.39
|View full text |Cite
|
Sign up to set email alerts
|

Chewing Xylitol Gum Improves Self-Rated and Objective Indicators of Oral Health Status under Conditions Interrupting Regular Oral Hygiene

Abstract: Chewing xylitol gum provides oral health benefits including inhibiting Streptococcus mutans plaque. It is thought to be especially effective in conditions where it is difficult to perform daily oral cleaning. Our study aim was to determine the effects of chewing xylitol gum on self-rated and objective oral health status under a condition interfering with oral hygiene maintenance. A randomized controlled intervention trial was conducted on 55 healthy ≥ 20-year-old men recruited from the Japan Ground Self Defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Participants were instructed to refrain from eating, drinking, or brushing their teeth at least 1 h prior to sampling. During sampling, participants were instructed to sit in a chair and chew gum free of sweeteners, food additives, and flavoring agents for 3 min, and stimulated saliva samples were collected in sterile plastic tubes, as previously described [18]. The saliva samples were stored at −80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to refrain from eating, drinking, or brushing their teeth at least 1 h prior to sampling. During sampling, participants were instructed to sit in a chair and chew gum free of sweeteners, food additives, and flavoring agents for 3 min, and stimulated saliva samples were collected in sterile plastic tubes, as previously described [18]. The saliva samples were stored at −80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrent with a more hydrophilic tooth surface after the chewing of gum was an improved mouthfeel perception in volunteers. Previous studies also showed that the chewing of gum created a self-perceived mouthfeel of 'a healthy oral cavity' (30,31) but these studies did not relate mouthfeel to the properties of the tooth surface or adsorbed salivary film composition. Chewing of the mastication control (Parafilm) also led to a reduction in the hydrophobicity of the tooth surface directly after chewing (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Research by Runnel et al [34] suggests that the efficacy of xylitol in caries prophylaxis may depend not only on the frequency of administration during the day but also on an even disposition of servings in time; also, a discontinuation of application, despite its latter resumption, might be significant. In conditions when retaining the usual routine of hygiene is impossible, chewing gum containing xylitol not only reduces the increment of bacteria in saliva but also improves the subjective evaluation of personal oral cavity condition [35]. According to the authors, both chewing gum and candies are recommended, considering the prolonged exposure time of the oral cavity to the xylitol contained.…”
Section: Discussionmentioning
confidence: 99%